126k views
3 votes
Insert parentheses to make a true equation 3+1*7-2^2*9-7=24

User Not A JD
by
4.9k points

1 Answer

1 vote

Answer:

(3+1)*(7-2^2)*(9-7) = 24

Explanation:

3+1*7-2^2*9-7

Now we give the parentheses to find out the result, that is, 24

(3+1)*(7-2^2)*(9-7)

Now we break the parentheses to calculate the result:

4*(7-2^2)*(9-7)

= 4*(7-4)*(9-7)

= 4*3*(9-7)

= 4*3*2

= 24

Therefore, if we give parentheses after each multiplication, we can get the desired result with the appropriate parentheses.

User H Krishnan
by
4.9k points